Upgrading of lobby and administration office of Slim River Country Resort for Majlis Daerah Tanjung Malim (MDTM) at Jalan Rumah Rehat, 35800 Slim River, Perak / Nor Atirah Abd Razak - Abd Razak, Nor Atirah (Faculty of Architecture, Planning and Surveying, 2011)
This project is about to upgrade lobby and administration office of Slim River Country Resort at Jalan Rumah Rehat, 35800 Slim River, Perak. The client for this project is Majlis Daerah Tanjung Malim (MDTM). This upgrading project is proposed based on investigation at the site and the client’s request too. The scope of this project is focusing on the lobby area and administration office which have strongly design issues based on space planning, the flow and also the condition of the area. To achieve the objectives of this project, that is to produce a welcoming environment to the surrounding, to upgrade the facilities for better services, to create new scheme as a new image for the resort and to re-organized space planning for better circulation, many ways have been taken. There are research, analysis, interview,observation and investigation in the process to identify the problems and the best solution for the problems. Through all the process of upgrading Slim River Country Resort, hopefully the objectives of the project will success and brings new changes to the resort and also increasing the quality of tourism industry.